Elements of attitude and motivation of SJKT Students at Form 1 in Malay Language Mastery - Marimothu, Gayatri; Kamaruddin, Rohaidah; Redzuan, Muhammad Alif (Human Resource Management Academic Research Society (HRMARS), 2024)
The study aims to investigate the attitudes, motivations, and interests of Form 1 students in six secondary schools in Negeri Sembilan towards learning Malay, particularly focusing on Indian students enrolled in SJKT. The findings sheds light on the factors influencing their proficiency in the Malay language. This research uses the Attitude Motivation Test Battery(AMTB) questionnaire by Gardner, 2005 which has been adapted to the objectives of this study. The analysis revealed that Indian students' attitudes towards learning Malay are predominantly influenced by affective components, indicating emotional aspects play a significant role in their language acquisition journey. This suggests that fostering positive emotions and attitudes towards learning Malay could potentially enhance language proficiency among SJKT students. Furthermore, the study identifies integrative motivation as the primary driving force for Indian students' motivation to learn Malay. Integrative motivation, which involves the desire to connect with and become part of the Malay-speaking community, emerged as a crucial factor influencing their language learning efforts. This underscores the importance of creating opportunities for SJKT students to engage with the Malay-speaking community and cultivate a sense of belonging. Overall, the findings suggest that addressing affective factors and promoting integrative motivation could be key strategies in improving the Malay language proficiency of SJKT students in Form 1. By understanding and addressing these factors, educators and policymakers can develop targeted interventions to support the language learning needs of Indian students in Negeri Sembilan's secondary schools.